Mengkaji Integrasi Peristiwa Terkini Dalam Kurikulum IPS Untuk Meningkatkan Relevansi Dan Keterlibatan Siswa dalam Pembelajaran - Nabila Putri Wahiddiyah; Desy Safitri; Sujarwo Sujarwo (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2024)
In an effort to enhance the relevance of learning and student engagement, the integration of events into the Social Science curriculum (IPS) has been the focus of attention. This research will examine methods and outcomes related to the integration of current events into the IPS curriculum and how it affects learning. By analyzing relevant literature, this study shows that integrating current events has great potential to improve students' understanding of IPS concepts, their motivation to learn, and their level of involvement in the learning process. Moreover, integrating recent events can help create a learning environment that is closer to the student's everyday life. However, issues such as the availability of resources and the balance between local and global issues must be addressed in order to integrate current events. The results of this study have significant consequences for those working in the field of education, especially IPS teachers in designing learning strategies that can enhance the relevance and involvement of students in IPS learning.